Determinants of Rural Household Income in Jiangxi, China - Fu Gonghua; Ge Zhijun (Hasanuddin University, 2014)
Both rural poverty and the huge urban-rural gap are serious problems in China. It needs to pay more attention to the rural society, the farmer, and the agriculture. This paper focused on the determinants of rural household’s income, and attempts to find out the factors which heavily impact on their income. This study showed that agricultural incomes only shares 22% of the household income averagely, while non-agricultural income takes another 78% among the sampled rural households. The labor wage income accounted for 71% of household income. The Gini coefficient of the household agricultural income per capita was 45.57%, and that of household non-agricultural income per capita was 37.79%, and both of them are higher than the Gini coefficient of household income per capita (28.91%). This was due to the household growing more crops (more agricultural income) than others who earned less income from non-agricultural sectors. The variance of the total household income per capita was smaller than that of both agricultural and non-agricultural income per capita. The study also find out that the Main Income Earner (MIE) worked inside the county, MIE’s education attainment, MIE’s non-agricultural skill attainment, the skill source from school education, job searching information from advertisement and Consumer-Producer ratio (CP ratio) were the main determinants which impact on household net income per capita significantly. In order to increase farmer households’ income and to alleviate the rural poverty, it is necessary to help farmers to attain more education, to give farmers useful offfarm skill training, and to supply more recruitment information service. Besides, it also needs to encourage those farmers in enhancing their ability to go to urban areas to find some jobs, including skill-training.